Using AI for forecasting and trading in markets : a study of deep learning and deep reinforcement learning in finance - Souza, João Paulo Costa e (2025)
Dissertação (mestrado)—Universidade de Brasília, Instituto de Ciências Exatas, Departamento de Ciência da Computação, Programa de Pós-Graduação em Informática, 2025.